4.4k views
3 votes
(05.01)

4^x = 8^x − 1
a. x=3/4
b. x=1
c. x=3
d. x=6
Algebra 2

2 Answers

7 votes

Answer:

c. x = 3

Explanation:

4^x = 8^(x-1)

2²^x = 2³^(x-1)

2^(2x) = 2^(3x-3)

2x = 3x - 3

x = 3

User Akalanka
by
5.2k points
1 vote

Answer:

c. x=3

Explanation:

4^x = 8^(x − 1)

4 = 2^2

8 = 2^3

2^2^x = 2^3^(x-1)

We know that a^b^c = a^(b*c)

2^(2x) = 2^(3*(x-1))

2^(2x) = 2^(3x-3)

The bases are the same so the exponents are the same

2x = 3x-3

Subtract 3x from each side

2x-3x = 3x-3-3x

-x = -3

x =3

User Yves Boutellier
by
4.7k points